Immunohistochemical analysis of molecular drivers in melanoma identifies p16 as an independent prognostic biomarker. Issue 6 (7th March 2014) - Lade-Keller, Johanne; Riber-Hansen, Rikke; Guldberg, Per; Schmidt, Henrik; Hamilton-Dutoit, Stephen Jacques; Steiniche, Torben
Abstract : Aims: To perform immunohistochemical (IHC) analysis of molecular drivers related to the development and maintenance of melanoma and to assess their value as diagnostic and prognostic melanoma biomarkers in routine clinical practice. Methods: Tissue microarrays constructed from a cohort of primary melanomas (n=355), benign naevi (n=37) and melanoma metastases (n=14) were evaluated for IHC expression of c-KIT, BRAF V600E, MITF, p16, p53 and PTEN, as well as for pERK, a surrogate marker for mitogen-activated protein kinase pathway activation. The results were correlated with clinicopathological parameters and clinical outcome. Results: Absent p16 expression and reduced MITF expression were both associated with the adverse prognostic markers ulceration (p=0.009 and p<0.0001, respectively), advanced tumour stage (p<0.0001 and p=0.001, respectively) and higher Breslow thickness (both p<0.0001), as well as with an adverse overall relapse-free survival (p<0.0001 and p=0.003, respectively). Absence of p16 expression predicted overall relapse-free (p=0.02) and distant metastasis-free (p=0.04) survival, independently of Breslow thickness, ulceration and tumour stage. Conclusions: IHC determined p16 expression is an independent prognostic biomarker of potential value in routine melanoma diagnostic practice.